Strengthening Viral Hepatitis Prevention and Control Through a One Health Approach (One Health & Risk Management, 2025)
Viral hepatitis remains a major global health challenge. The WHO Global Hepatitis Report 2024 estimates that 254 million people are living with hepatitis B, and 50 million people have hepatitis C worldwide. Hepatitis B and hepatitis C are deadly communicable diseases, with 2.2 million new infections recorded in 2022.Global prevalence of hepatitis A, hepatitis D, and hepatitis E varies by region and risk factors. Hepatitis A and hepatitis E are transmitted through contaminated food and water, while hepatitis D occurs only in individuals already infected with hepatitis B or newly infected with hepatitis B and hepatitis D concurrently. The zoonotic nature of hepatitis E has been observed in industrialized and middle-income countries, and the One Health approach, recognizing the interdependence of human, animal, and environmental health, provides a valuable framework for tackling this infection.Laboratory diagnostics play a central role in early detection, prevention, control, and elimination through timely vaccination and treatment. Leveraging One Health infrastructure catalyzes the laboratory potential. New serodiagnostic platforms and Point-of-Care (POC) testing facilitate more efficient decentralized screening, enhancing public health efforts in prevention, control, and elimination. Advanced molecular characterization and surveillance improve viral identification and resistance profiling.The One Health and Risk Management framework fosters informed decision-making through multidisciplinary research, case studies, and surveillance strategies.I commend the editorial team and contributors, and urge continued collaboration between laboratories, academia, clinicians, and public health authorities. Only through joint, evidence-based efforts can we advance the fight against viral hepatitis.